2019
DOI: 10.1103/physrevb.99.035441
|View full text |Cite
|
Sign up to set email alerts
|

Gate-tunable magnetism of C adatoms on graphene

Abstract: We have performed density functional theory calculations of graphene decorated with carbon adatoms, which bind at the bridge site of a C-C bond. Earlier studies have shown that the C adatoms have magnetic moments and have suggested the possibility of ferromagnetism with high Curie temperature. Here we propose to use a gate voltage to fine tune the magnetic moments from zero to 1 µB while changing the magnetic coupling from antiferromagnetism to ferromagnetism and again to antiferromagnetism. These results are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…A recently published paper showed that gate-tunable magnetism could even be attained by putting C adatoms in the graphene structure. 9 When the impurity spins couple with the conduction electron spins, as shown in Fig. 1 , different kinds of magnetism, like paramagnetism, ferromagnetism, antiferromagnetism or spin glass type behavior, can be obtained in 2D carbon based composites according to the coupling of the spins within the material.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published paper showed that gate-tunable magnetism could even be attained by putting C adatoms in the graphene structure. 9 When the impurity spins couple with the conduction electron spins, as shown in Fig. 1 , different kinds of magnetism, like paramagnetism, ferromagnetism, antiferromagnetism or spin glass type behavior, can be obtained in 2D carbon based composites according to the coupling of the spins within the material.…”
Section: Introductionmentioning
confidence: 99%
“…The energy levels of the R.Ti 15 La 2þ O 31 and A.Ti 15 La 2þ O 31 systems were split. This finding is due to Stoner's theory, [33] which shows that when the external magnetic field h = 0, if the number of upspin and downspin electrons is not equal, n " 6 ¼ n # . As shown in Figure 3e, the built-in magnetic field and multibody effect in the A.Ti 15 La 2þ O 31 system were greater than the Burstein-Moss effect in the system; therefore, the bandgap in the A.Ti 15 La 2þ O 31 system became narrower.…”
Section: Structure Formation Energy and Total Magnetic Momentmentioning
confidence: 90%